Comparing the influence of surgical and conservative therapy on quality of life in patients with early-stage medication-related Osteonecrosis of the jaw - a prospective longitudinal study - Rückschloß, Thomas; Smielowski, Maximilian; Moratin, Julius; Schnug, Gregor; Appel, Maximilian; Münch, Philipp; Bleymehl, Moritz; Zittel, Sven; Engel, Michael; Hoffmann, Jürgen; Ristow, Oliver (Medicina, 2023)
Background and Objectives: The purpose of this study was to evaluate the impact of surgical and conservative, non-surgical treatment on general health-related (QoL) and oral health-related quality of life (OHRQoL) in patients suffering from AAOMS stage I MRONJ. Materials and Methods: In the course of this prospective clinical study, QoL and OHRQoL using QLQ-C30 and QHIP G14 questionnaire were longitudinally assessed in N = 174 prospectively enrolled patients with indication of treatment of MRONJ stage I over a period of 12 months. Patients received conservative or surgical treatment. The measurement time points were preoperatively (T0), 12 weeks (T1), 6 months (T2) and 1 year after operation (T3). Results: For OHRQoL, no significant (p > 0.05) differences were found between both treatment groups for all timepoints (T0-T3). In the surgical treatment group, OHIP scores of T1, T2 and T3 were significantly lower than baseline measures (T0) (T0-T1 (2.99, p = 0.024), T0-T2 (5.20, p < 0.001), T0-T3 (7.44, p < 0.001)). For conservative treatment group OHIP, scores of T2 and T3 were significantly lower than baseline measures (T0) (T0-T2 (9.09, p = 0.013), T0-T3 (12.79, p < 0.001)). There was no statistically significant effect of time on QLQ-C30 scores in both groups (surgical treatment: F(3, 174) = 1.542, p < 0.205, partial η2 = 0.026; conservative treatment: F(3, 30) = 0.528, p = 0.667, partial η2 = 0.050). QLQ-C30 scores turned out to be significantly lower in the non-surgical group at T1 (p = 0.036) and T3 (p = 0.047) compared to the surgical treatment group. Conclusions: Surgical and conservative treatment of MRONJ stage I significantly improves patients’ OHRQoL. Surgical treatment is superior to conservative treatment of MRONJ stage I regarding general QoL. Therefore, surgical treatment of MRONJ stage I should not be omitted for QoL reasons.